Richness, species composition and functional groups in Agaricomycetes communities along a vegetation and elevational gradient in the Andean Yungas of Argentina - Eduardo, Nouhra; Florencia, Soteras; Nicolás, Pastor; József, Geml (Biodiversity and conservation, 2018)
The Neotropics are among the least explored regions from a mycological perspective. A few recent molecular studies in South America have shown high fungal diversity as well as numerous groups of mostly undescribed taxa. Through soil metabarcoding analysis we compared richness and species composition among macrofungal communities, belonging to Agaricales, Russulales, Boletales and Phallomycetidae groups, in three elevational forests types in the subtropical Yungas of Northwestern Argentina (Piedmont forest; Montane forest, Montane cloud forest). The aims of this study were to assess richness of taxonomic and functional groups along the elevation gradient and to assess the relationships between environmental variables and species composition in the studied fungal communities. The results have shown rich Agaricomycetes communities, diversely structured among forests habitats. The elevation gradient differentially affected the richness and distribution of Agaricales, Russulales, Boletales and Phallomycetidae. Based on fungal trophic modes and guilds, the gradient also affected the ectomycorrhizal taxa distribution. When considering the basidiomata growth forms (agaricoid, boletoid, gasteroid, etc.), only the secotioid type showed significant elevational differences. Additional analyses indicated that saprotrophic nutritional mode was dominant along the entire gradient, being partially replaced by biotrophic modes at higher elevations. Fungal communities in the Montane cloud forests are most dissimilar when compared with communities at the Piedmont forest and Montane forest, which is consistent with the different biogeographic origins of these forests. DNA metabarcoding sequence analysis provided detailed information on the diversity and taxonomic and functional composition of macrofungal communities.